A practical treatise on bridge-construction being a text-book on the design and construction of bridges in iron and steel : for the use of students, draughtsmen and engineers - Fidler, T. Claxton 1841-1917 (Charles Griffin, 1901)
Examining the practice of bridge construction and the experimental facts on which it is based, this work states the theory of bridge-construction in such a practical form as will be most useful for the purposes to which it is employed.